Podstawy prawne dyscypliny pracy w Tolniczych spółdzielniach produkcyjnych - Strugała, Jerzy R. (Wydział Prawa i Administracji UAM, 1983)
The work discipline in agricultural collective farms is indispensable in obtaining there good productional results. The agricultural collective farms are operated by means of labor of its members (i.e. members of the cooperative), their families and employees. The legal situation of members of the collective body is regulated either in cooperative law or in labor law. The coperative law does not offer any regulation of the work discipline in collective enterprises, on the other hand, the application of labor law to members of cooperatives and their families in very limited. Yet, some uniform rules of work discipline for all the members of a collective body have to be established in order to provide the effective, work. Cooperative statutes, regulations and decisions of cooperative organs are aimed at pursueing this goal. The regulation of work discipline adopted in internal normative acts of a cooperative is in many instances patterned on the legal institutions of common labor law. That usage of patterns of legal solutions put to tests in the long practice of labor law application can be correct, provided that particular rules of collective farm functioning are taken account of.
Legal foundations of the work discipline in agricultural collective farms